Tandem Bullet Homicide - Prahlow, Samuel P. (Acad Forensic Pathol, 2016)
The phenomenon referred to as “tandem bullets” occurs when two (or more) projectiles are expelled from a firearm barrel in a single pull of the trigger. A “tandem gunshot wound” occurs when tandem bullets produce injuries. Several scenarios can occur, including the occurrence of multiple entrance wounds produced by separate tandem projectiles as well as a single entrance wound through which multiple tandem projectiles enter the body. We present a case of homicide by tandem bullets in which two tandem bullets entered a single entrance wound, with one projectile exiting the body and one remaining within the body. In addition, we review the topic of tandem projectiles and summarize other situations that may cause initial confusion when attempting to account for all gunshot wounds on the skin and projectiles as viewed on pre-autopsy imaging.